STRATEGI GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR PESERTA DIDIK PENDIDIKAN AGAMA ISLAM BERDASARKAN TEORI KONSTRUKTIVISME DI SMAN I BELITANG II - Erlianti, Dela; Sodikin, Ahmad; Ikhsanudin, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of enhancing students’ learning motivation in Islamic Religious Education (PAI), as motivation significantly influences students’ learning outcomes and engagement. The problem identified is the varying levels of student motivation, where some students are active while others remain passive during the learning process. Therefore, this study aims to analyze the strategies employed by PAI teachers in fostering students’ learning motivation based on constructivist theory at SMAN I Belitang II. This research uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The informants include the vice principal for curriculum affairs, PAI teachers, and students. The findings reveal that teachers implement constructivist-based strategies such as Problem Based Learning (PBL), group discussions, contextual teaching related to daily life, and the use of diverse learning resources. In addition, teachers act as facilitators and motivators by providing guidance, encouragement, and opportunities for students to actively participate in the learning process. These strategies have been proven to increase students’ activeness, participation, and overall learning motivation in PAI subjects. Supporting factors include teacher creativity and student engagement, while inhibiting factors involve differences in students’ abilities, limited time, and uneven participation. Overall, the application of constructivist-based strategies contributes positively to improving students’ learning motivation and creating a more meaningful and student-centered learning environment.